Impact of white‐spotting alleles, including W20, on phenotype in the American Paint Horse. (20th July 2020) - Brooks, S. A.; Palermo, K. M.; Kahn, A.; Hein, J.
Summary: The American Paint Horse Association (APHA) records pedigree and performance information for their breed, a stock‐type horse valued as a working farm or ranch horse and as a pleasure horse. As the name implies, the breed is also valued for its attractive white‐spotting patterns on the coat. The APHA utilizes visual inspections of photographs to determine if coat spotting exceeds threshold anatomical landmarks considered characteristic of desirable patterns. Horses with sufficient white patterning enter the 'Regular' registry, rather than the 'Solid Paint‐Bred' division, providing a threshold modeled phenotype. Genetic studies previously defined sequence variants corresponding to 35 alleles for white spotting in the horse. Here, we calculate the allele frequencies for nine common white‐spotting alleles in the American Paint Horse using a sample of 1054 registered animals. The APHA spotting phenotype is altered by additive interactions among spotting loci, and epistatically by the MC1R and ASIP genes controlling pigment production. The W20 allele within the KIT gene, independent of other known spotting alleles, was strongly associated with the APHA‐defined white‐spotting phenotype ( P  = 1.86 × 10 −18 ), refuting reports that W20 acts only as a modifier of other underlying white‐spotting patterns. The parentage of an individual horse, either American Paint or American Quarter Horse, did not alter the likelihood of its entering the APHA Regular Registry. An empirical definition of the action of these genetic loci on the APHA‐defined white‐spotting phenotype will allow more accurate application of genome‐assisted selection for improving color production and the marketability of APHA horses.